TINJAUAN YURIDIS TERHADAP JUAL BELI TANAH DAN BANGUNAN YANG DIBEBANI HAK TANGGUNGAN - Kiki Anggriyani; Erlina; ST Nurjannah (Alauddin Law Development Journal)
The bank is very careful in the case of selling objects of mortgages under the hand because it must refer to Article 1320 of the Civil Code as a legal condition for an agreement, the bank prefers the execution of collateral through auction rather than selling the object of underwriting because according to the bank it does not have strong legal force. The method used in this research is empirical research. The empirical normative research method is the implementation of laws in an event in the field.The results of this study indicate that the bank is very careful in the case of selling objects of liability under the hand, the bank prefers the execution of collateral through the auction rather than selling the object of mortgage under the hand, because according to the bank it has no legal force which is strong, can harm the bank, and is very vulnerable to problems if it really happens